Review of creditor protection in Malaysia - Hasani Mohd Ali, (Fakulti Undang - Undang, 2005)
Creditor protection may be afforded through statutory provisions or case law; either within the framework of directors’ duties or through other measures. This article will show that creditors in Malaysia especially those unsecured ones deserve more protection as the law is still unclear or not supportive enough to protect creditor interests